2018
DOI: 10.7150/thno.27221
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound molecular imaging as a non-invasive companion diagnostic for netrin-1 interference therapy in breast cancer

Abstract: In ultrasound molecular imaging (USMI), ligand-functionalized microbubbles (MBs) are used to visualize vascular endothelial targets. Netrin-1 is upregulated in 60% of metastatic breast cancers and promotes tumor progression. A novel netrin-1 interference therapy requires the assessment of netrin-1 expression prior to treatment. In this study, we studied netrin-1 as a target for USMI and its potential as a companion diagnostic in breast cancer models.Methods: To verify netrin-1 expression and localization, an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Nanobubble CSF-1R had an average size of about 428 nm and were ultrasound-visible even at 20 MHz both in vitro and in vivo ; imaging was still viable even when diluted 2000 times. Notably, NBs were administered at a low concentration compared with our previous research and other studies ( Wischhusen et al, 2018 ), a technique which can be employed to reduce the level of background signal and modulate facilitate the comparison of heterogeneous tumor models ( Wang et al, 2010 , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nanobubble CSF-1R had an average size of about 428 nm and were ultrasound-visible even at 20 MHz both in vitro and in vivo ; imaging was still viable even when diluted 2000 times. Notably, NBs were administered at a low concentration compared with our previous research and other studies ( Wischhusen et al, 2018 ), a technique which can be employed to reduce the level of background signal and modulate facilitate the comparison of heterogeneous tumor models ( Wang et al, 2010 , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Xu explored the dual-targeting capability of this novel contrast agent further and found that dual-targeted agent had more intense signal than single-targeted agent [16]. Wischhusen created netrin-1 microbubbles as a potential diagnostic and therapeutic marker for interference therapy in breast cancer [17].…”
Section: Lipid Bilayermentioning
confidence: 99%
“…Contrast-enhanced ultrasound (CEUS) combining ultrasound contrast agents (UCAs) and contrast-specific imaging techniques has already become a valuable clinical technique for assessing hepatic perfusion after OLT due to its advantages including no ionizing radiation, real-time detection, and reproducibility 8 , 9 . As an important branch of CEUS, molecular ultrasound (US) imaging has emerged as a new method for visualizing molecular targets using ligand-functionalized microbubbles (MBs), thus providing anatomical and functional information simultaneously with high sensitivity and specificity 10 , 11 . Currently, molecular US imaging is widely used in preclinical research and has shown good accuracy 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%